Retracted: INTEGRASI PAJAK DAN ZAKAT DI INDONESIA PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF - Editor El-Jizya (Fakultas Ekonomi dan Bisnis Islam (FEBI), Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2019)
This paper was retracted by Fakultas Ekonomi dan Bisnis Islam as Publisher on August 8, 2019. This paper was published due to a technical error and was not intended to be included in this journal. This article is the property of Masnun Tahir & Zasiana Elly Triantini, which has been published in the journal Al-Adalah Faculty of Sharia UIN Raden Intan Lampung volume 12 number 1 in 2015 at http://ejournal.radenintan.ac.id/index.php/adalah/article/view/204/374. Thus the article belongs to Moh. Abdur Rohman Wahid was not published by us. Retractions are published on August 8, 2019.